Growing Teratoma Syndrome. (17th August 2014) - Scavuzzo, Anna; Santana Ríos, Zael Arturo; Noverón, Nancy Reynoso; Jimenez Ríos, Miguel Angel
Abstract : Growing teratoma syndrome (GTS) is a rare clinical entity, which presents with enlarging teratomas masses of the retroperitoneum or other locations, occurring during or after systemic chemotherapy for the treatment of nonseminomatous germ cell of the testis (NSGCT), with normalised tumour markers. Awareness of this syndrome is necessary in order to prevent unnecessary chemotherapy and allow optimal management. Prognosis is excellent after the excision of these tumors, but surgery has to be as complete as possible. Surgical resection of bulky GTS lesions is technically challenging; intraoperative complications may occur; that is, why the treatment must not be delayed. Our experience in the surgical management of these lesions is reviewed in the following work.